Factores biopsicosociales (físico, social, cultural y psicológico) que influyen en la anorgasmia/orgasmo en las relaciones sexuales de mujeres (2020)
The research entitled "Biopsychosocial factors (physical, social, cultural and psychological) that influence anorgasmia / orgasm in the sexual relations of women" seeks to understand these factors, taking into account biological, social, cultural and religious aspects, which have been established throughout history, including the taboo towards sexuality and beliefs, as well as the dynamics within family and couple relationships that have influenced sexual behavior and pleasure in women. For this, it counted with the voluntary participation of four women who have had a stable partner and with whom they have lived, residents of Cartago - Valle del Cauca. The research was carried out using a qualitative methodology, with a hermeneutical historical focus, narrative design and with a descriptive scope, using a semi-structured interview that obeyed the categories that were part of the developed theoretical foundations. Among the results of the biopsychosocial factors that affect the anorgasmia / orgasm, it was found that the absence of stimulus prior to intercourse can decrease lubrication and cause pain during friction and, in turn, make orgasm impossible, as well as the lack of knowledge of own body, the rejection of the conception of sex as sin, and beliefs and norms were found that limit the sexuality of women.